2023
DOI: 10.1111/joim.13740
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of human longevity: From variants to genes to pathways

Larissa Smulders,
Joris Deelen

Abstract: The current increase in lifespan without an equivalent increase in healthspan poses a grave challenge to the healthcare system and a severe burden on society. However, some individuals seem to be able to live a long and healthy life without the occurrence of major debilitating chronic diseases, and part of this trait seems to be hidden in their genome. In this review, we discuss the findings from studies on the genetic component of human longevity and the main challenges accompanying these studies. We subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 127 publications
0
3
0
2
Order By: Relevance
“…Ein Gen, für das der Zusammenhang mit Langlebigkeit in vielen unabhängigen Studien repliziert wurde, ist APOE , das für Apolipoprotein E (Apo-E) codiert [ 3 , 16 ]. Apo‑E ist ein Strukturbestandteil von Lipoproteinen, die für den Transport von Cholesterin und Triglyceriden im Blut zuständig sind.…”
Section: Genvarianten Mit Auswirkungen Auf Die Lebenserwartungunclassified
See 1 more Smart Citation
“…Ein Gen, für das der Zusammenhang mit Langlebigkeit in vielen unabhängigen Studien repliziert wurde, ist APOE , das für Apolipoprotein E (Apo-E) codiert [ 3 , 16 ]. Apo‑E ist ein Strukturbestandteil von Lipoproteinen, die für den Transport von Cholesterin und Triglyceriden im Blut zuständig sind.…”
Section: Genvarianten Mit Auswirkungen Auf Die Lebenserwartungunclassified
“…Neben APOE konnte in genetischen Studien auch für das FOXO3 -Gen eine Verbindung zur Langlebigkeit reproduzierbar nachgewiesen werden [ 3 , 16 , 19 , 20 ]. Der durch FOXO3 codierte Transkriptionsfaktor ist Teil eines evolutionär konservierten Regulationsnetzwerks, das durch Insulin und den insulinähnlichen Wachstumsfaktor 1 gesteuert wird und dessen Aktivität negativ mit der Lebensspanne korreliert [ 1 , 2 ].…”
Section: Genvarianten Mit Auswirkungen Auf Die Lebenserwartungunclassified
“…According to Perls et al, siblings of long-lived individuals are 17 and 8 times more likely, respectively, to reach the same age than the population average [112]. This means that human longevity may be associated with genetic variants that are rare in the population [113][114][115], although variants that are common in the population are also important for longevity [116,117].…”
Section: Heritability Of the Lifespan Trait In Fliesmentioning
confidence: 99%
“…Since the world is facing ageing of the global population, with the proportion of elderly expected to almost double by 2050 ( World Health Organization, 2023 ), the importance of research on this topic has never been greater. Most basic ageing mechanisms and candidate genes that affect them were discovered in model organisms ( Antebi, 2007 ), but many retain the same function in humans due to high conservation of those genes among species ( Smulders and Deelen, 2023 ). Research into these mechanisms is essential for a better understanding of what drives the ageing process, as well as for discovering the factors that contribute to successful ageing and longevity.…”
Section: Introductionmentioning
confidence: 99%
“…Age is a major risk factor for developing age-related chronic conditions ( Niccoli and Partridge, 2012 , Dillin et al, 2014 , Hou et al, 2019 ), which is why genes modulating the risk for chronic disease have also been studied as candidate genes for longevity. The most well-known example is the APOE gene – associated with the risk for cardiovascular diseases ( Eichner et al, 1993 , Wilson et al, 1994 , Bennet et al, 2007 ) and Alzheimer’s disease ( Zuo et al, 2006 , Farrer et al, 1997 ) – which was first identified in candidate gene studies and later confirmed in genome-wide association studies (GWAS) as the most important genetic factor influencing longevity ( Smulders and Deelen, 2023 ).…”
Section: Introductionmentioning
confidence: 99%